2020
DOI: 10.21043/qijis.v8i1.6430
|View full text |Cite
|
Sign up to set email alerts
|

The role of Cirebon Women Ulama in Countering Religious Radicalism

Abstract: <p>The trend in terrorist acts nowadays is using women as <em>perpetrators with a feminine approach. To respond to the condition, the figure of the Cirebon women ulama takes a very significant role. When women could be recruited as terrorists, it should be easier too to get them back to become agents of peace. This study originally attempts to describe the experiences and efforts of Cirebon women ulama in the process of socio-religious transformation in the Cirebon society towards a better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…This finding is in line with the results of research by Gumiandari and Nafi'a [55]. It showed that building religious networks and developing religious literacy between institutions of various social communities suppress the development of radical understanding in the midst of society, including educational institutions.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is in line with the results of research by Gumiandari and Nafi'a [55]. It showed that building religious networks and developing religious literacy between institutions of various social communities suppress the development of radical understanding in the midst of society, including educational institutions.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, the reward power that the teacher carries out in learning with a multicultural perspective is carried out by giving rewards. (Gumiandari & Nafi'a, 2020) Reward power, in this case, is in the form of power to give positive benefits or rewards to those who are led. Of course, this can be done in that the leader has the ability and resources to reward subordinates who follow his directions.…”
Section: Coercive and Reward Powermentioning
confidence: 99%
“…Every post on social media reflects the owner's religious literacy. Gumiandari said "… religious literacy is an open attitude towards and knowing the values in other religions" [12]. This religious literacy needs to know its emergence both in terms of the reference sources used and the accompanying inspiration.…”
Section: Religious Literacy Social Media Activist Millennial Generatimentioning
confidence: 99%